Combination Therapy of Adalimumab With an Immunomodulator Is Not More Effective Than Adalimumab Monotherapy in Children With Crohn's Disease: A Post Hoc Analysis of the PAILOT Randomized Controlled Trial. Issue 11 (3rd December 2019) - Matar, Manar; Shamir, Raanan; Turner, Dan; Broide, Efrat; Weiss, Batia; Ledder, Oren; Guz-Mark, Anat; Rinawi, Firas; Cohen, Shlomi; Topf-Olivestone, Chani; Shaoul, Ron; Yerushalmi, Baruch; et al.
Abstract: Background: The PAILOT trial was a randomized controlled trial aimed to evaluate proactive vs reactive therapeutic drug monitoring in children with Crohn's disease (CD) treated with adalimumab. Our aim in this post hoc analysis of the PAILOT trial was to assess the efficacy and safety of adalimumab combination treatment in comparison with monotherapy at week 72 after adalimumab induction. Methods: Participants were children 6–17 years old, biologic naïve, with moderate to severe CD, who responded to adalimumab induction at week 4. Patients receiving immunomodulators at baseline maintained a stable dose until week 24; patients could then discontinue immunomodulators. At each visit, patients were assessed for disease index, serum biomarkers, fecal calprotectin, adalimumab trough concentration, and anti-adalimumab antibodies. Results: Out of the 78 patients (29% female; mean age, 14.3 ± 2.6 years), 34 patients (44%) received combination therapy. During the study period, there was no significant difference in the rates of sustained corticosteroid-free clinical remission (25/34, 73%, vs 28/44, 63%; P = 0.35) or sustained composite outcome of clinical remission, C-reactive protein ≤0.5 mg/dL, and calprotectin ≤150 µg/g (10/34, 29%, vs 14/44, 32%; P = 0.77) between the combination group and the monotherapy group, respectively. Clinical and biological outcomes did not differ between the proactive and reactive subgroups within the combination and monotherapy groups. Adalimumab trough concentrations and immunogenicity were not significantly different between groups. The rate of serious adverse events was not significantly different between groups but was numerically higher in the monotherapy group. Conclusions: Combination therapy of adalimumab and an immunomodulator was not more effective than adalimumab monotherapy in children with CD (ClinicalTrials.gov No. NCT02256462). Abstract : In an analysis of 78 children with Crohn's disease followed prospectively for 72 weeks from adalimumab initiation, we found that combination therapy of adalimumab and an immunomodulator was not more effective than adalimumab monotherapy.